Why should ACP countries give high priority to S&T - Barnett, Audia (Technical Centre for Agricultural and Rural Cooperation, 2004)
National development is driven by a multiplicity of factors, ranging from the natural and human resource base to macroeconomic policies and trade. These factors are in turn sensitive to many other externalities, including social or political conditions at regional and international levels. In short, national development is directed by and yet extremely vulnerable to the vagaries of the world. At the international level, many economic and geographical alliances are emerging, all of which are linked by a common language, S&T. Can S&T positively influence national development in ACP countries? The answer is a resounding YES.